1998
DOI: 10.1093/ageing/27.6.677
|View full text |Cite
|
Sign up to set email alerts
|

Carotid disease in acute stroke

Abstract: these findings suggest that ipsilateral carotid disease is an important cause of stroke for those with anterior circulation infarcts but not for those with LACI or POCI. Subjects with PACI should be referred for early carotid imaging to identify those with severe disease who may be suitable for elective carotid surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…[2][3][4][5] Carotid disease and cardiac sources of emboli are more common in total and partial anterior circulation infarcts (TACIs and PACIs, respectively) than in lacunar (LACIs) and posterior circulation infarcts (POCIs). 6,7 While numerous studies have examined intracranial arterial velocities in middle cerebral artery (MCA) stroke, 8 -13 only 2 (of 32 and 85 patients, respectively) have investigated the relationship between the OCSP classification and patterns of vascular occlusion. 14,15 Both demonstrated that those with TACIs were more likely than the other subtypes to have occlusion of the MCA, and those with LACIs were unlikely to have intracranial large-vessel disease.…”
mentioning
confidence: 99%
“…[2][3][4][5] Carotid disease and cardiac sources of emboli are more common in total and partial anterior circulation infarcts (TACIs and PACIs, respectively) than in lacunar (LACIs) and posterior circulation infarcts (POCIs). 6,7 While numerous studies have examined intracranial arterial velocities in middle cerebral artery (MCA) stroke, 8 -13 only 2 (of 32 and 85 patients, respectively) have investigated the relationship between the OCSP classification and patterns of vascular occlusion. 14,15 Both demonstrated that those with TACIs were more likely than the other subtypes to have occlusion of the MCA, and those with LACIs were unlikely to have intracranial large-vessel disease.…”
mentioning
confidence: 99%
“…The prevalence of significant stenosis in studies conducted in Western population was about 14% (2) and 21%. (3) This variation could be due to racial differences. (4,5) Extracranial carotid artery stenosis was more commoner in whites and men.…”
Section: Discussionmentioning
confidence: 99%
“…3 Carotid ultrasonography combines B mode ultrasound image with a doppler ultrasound assessment of blood flow velocity. These plaques alter the blood flow haemodynamics and increase the systolic flow velocity.…”
Section: Introductionmentioning
confidence: 99%
“…In most of these studies, carotid artery disease was found to be significantly less frequent in patients with lacunar strokes compared with nonlacunar strokes. [31][32][33][34][35][36] The frequency of carotid disease in lacunar strokes has been considerably variable in different studies, ranging from 3% to 39%, [31][32][33][34][35][36][37][38][39][40][41] although it must be noted that the methodology used to both classify lacunar infarcts as well as to detect carotid disease also varied widely. A study of 726 patients with anterior circulation transient ischemic events or infarcts, excluding total anterior circulation infarcts, revealed a negative association of severe carotid stenosis with lacunar events.…”
Section: Carotid Artery Disease and Lacunar Infarctsmentioning
confidence: 99%